Catalytic Oxidation of Indigo Carmine in the Presence of Silver Nanoparticles: Application to Groundwater Analysis. Issue 2 (29th October 2012) - Sahraei, R.; Cheraghi, J.; Hushmandfar, R.; Abbasi, S.; Mortazavi, S. S.; Noorizadeh, H.; Farmany, A.
Abstract The oxidation of indigo carmine by potassium hexacyanoferrate(III) is catalyzed by trace of silver nanoparticle (AgNP). The reaction is followed UV‐Vis absorption spectrophotometrically by measuring the change in the absorption spectra (λmax 612 nm). The catalytic oxidation reaction is used for the quantification of indigo carmine. The calibration graph was linear in the concentration range 50 nM—1.8 μM of indigo carmine. The variables affecting the method have been optimized. The method is applied to the determination of indigo carmine in groundwater samples with the satisfactory results.